Mental health and sleep in the post-COVID-19 era among Thai undergraduate students - Sineenart Chautrakarn; Ekachai Jaiprom; Parichat Ong-Artborirak (Scientific Reports)
Abstract The purpose of this study was to examine mental health problems and sleep quality among undergraduate students in the post-COVID-19 era, as well as related factors. This cross-sectional study involved 627 undergraduate students from Chiang Mai University in northern Thailand between October and December 2022. Data were collected using a self-administered online questionnaire that included the General Health Questionnaire-12 (GHQ-12), the Center for Epidemiologic Studies-Depression Scale (CES-D), and the Pittsburgh Sleep Quality Index (PSQI). The study found that 57.9% of participants experienced mental health problems (95% CI: 54.0–61.8), 32.2% experienced depression (95% CI: 28.5–35.9), and 68.1% reported poor sleep quality (95% CI: 64.4–71.8). Multiple logistic regression analysis revealed that medical conditions, relationships with family members, relationships with friends or other people, having problems while studying at university, and self-perceived COVID-19 impact score were all associated with mental health problems and poor sleep quality (p < 0.05). Depression was associated with the field of study, relationships with family members, relationships with friends or other people, having problems while studying at university, and self-perceived COVID-19 impact score (p < 0.05). The findings highlight a significant occurrence of poor sleep and mental health issues, including depression, among undergraduate students in the post-COVID-19 era, underscoring the need for ongoing mental health monitoring and interventions to mitigate negative outcomes.